Which firm's characterization induce shift or bias effects when new innovations?. Evidence from manufacturing sector in Colombia (2017)
"Finding the determinants of the total factor productivity at a firm level helps to understand and analyze more deeply the technological changes and its direction. The type of innovations a firm would have access will differ within the sector because a firm?s characteristic and possibilities. This following research shows that large firms have the capacity to do support their research and development process to induce neutral technological change in general represented as a shift effect on the production function. While small firm lack this capacity and dedicate their internal fund to imitate leaders and improve their process inducing bias technological change, a bias effect on the production function isoquants." -- Tomado del Formato de Documento de Grado.